Oxidation-reduction potential affects medium-chain fatty acid ethyl ester production during wine alcohol fermentation. (July 2022) - Xue, Shi-Jin; Zhang, Jia-Rui; Zhang, Rui-Xia; Qin, Yi; Yang, Xiao-Bing; Jin, Guo-Jie; Tao, Yong-Sheng
Graphical abstract: Oxidation-Reduction Potential Affects Medium-Chain Fatty Acid Ethyl Ester Production during Wine Alcohol Fermentation. Highlights: MCFAEEs reached the maximum under 0 mV compared to other ORPs. High citric acid flux to cytoplasm and moderate NADP + /NADPH were found under 0 mV. High expressions of ACC1, FAS1, FAA2 and EEB1 favored for MCFAEEs synthesis. Low expression of POX1 alleviated the decrease of MCFAEEs under 0 mV at 204 h. Abstract: The medium-chain fatty acid ethyl esters (MCFAEEs) are a group of important aroma compounds generated during wine production. Wine alcohol fermentation involves several redox processes, which are affected by the oxidation–reduction potential (ORP). However, the mechanism via which ORP regulates MCFAEE production remains unclear. To investigate the effect of ORP on MCFAEE production, wine alcohol fermentation was performed using Saccharomyces cerevisiae under different ORPs. The results demonstrated that the ORPs studied (except for 90 mV) did not significantly affect cell growth, sugar consumption, and ethanol production, while the MCFAEE concentration in the simulated wines can be manipulated by ORP operation. MCFAEE levels increased till 96 h, and then decreased. The maximum MCFAEE level of 1222.97 μg/L was obtained after 96 h at 0 mV, which was 45.32% higher than that of the control. During the increase, higher relative expression of ACC1, FAS1, FAA2 and EEB1, elevated external citric acid flux, and moderate intracellular NADP + /NADPH ratio were observed at 0 mV compared to that at other ORPs. During the decrease, lowest relative expression of POX1 was detected at 0 mV. We showed for the first time the relationship between ORP operation and MCFAEE production in winemaking, which will improve the aroma quality of wine.